2021
DOI: 10.3389/fmed.2021.684594
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Anamnestic Data in the Management of Clostridium Tetani Infection in Elderly

Abstract: Background: Tetanus infection remains a significant complication of wounds. Because most tetanus treatment guidelines rely on anamnestic data collected directly from patients, the congruence between anamnesis and laboratory evidence must be verified, especially in the elderly population.Aim: Assess, in both the geriatric population (>65) and the non-geriatric one, the reliability of anamnestic data for managing patients with tetanus-risk wounds, identified categories of populations most exposed to non-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…An Italian research group has demonstrated that, in the years of activity of an OBI (osservazione breve intensiva, unit of short and intensive observation) Team, which had the function of flow coordination, stabilization of complex patients, boarding management, and bed management, a stabilization of boarding and exit block phenomena were observed, despite the increasing number of ED visits and the need for hospitalization of the patients themselves. A containment of LOS times and an improvement in the outcome of some categories of patients was observed as well [81][82][83][84][85][86][87][88]. These findings were in line with data from several other European and American research groups [89][90][91][92][93][94].…”
Section: Microlevel Strategiessupporting
confidence: 82%
“…An Italian research group has demonstrated that, in the years of activity of an OBI (osservazione breve intensiva, unit of short and intensive observation) Team, which had the function of flow coordination, stabilization of complex patients, boarding management, and bed management, a stabilization of boarding and exit block phenomena were observed, despite the increasing number of ED visits and the need for hospitalization of the patients themselves. A containment of LOS times and an improvement in the outcome of some categories of patients was observed as well [81][82][83][84][85][86][87][88]. These findings were in line with data from several other European and American research groups [89][90][91][92][93][94].…”
Section: Microlevel Strategiessupporting
confidence: 82%
“…Because of these changes, treatment and observation paths have been designed for pathologies that are also very complex or with complex management, such as, for example, severe trauma, heart failure and head trauma. [89][90][91][92][93][94][95]. Although increased crowding negatively affects patient outcomes and satisfaction, the consequences for triage-particularly on wait times and UT and OT frequency-have not yet been extensively investigated.…”
Section: Overallmentioning
confidence: 99%
“…Savioli et al . 54 reported that many individuals are not aware of their vaccination history; this is especially the case among the elderly who are reported to be less aware of their vaccination history. Thus, the elderly is a target group for whom TQS could be useful in identifying tetanus morbidity risk according to their study.…”
Section: Reviewmentioning
confidence: 99%
“…Considering the effective use of resources during times of disaster, the risk identification shown in Table 4 may be challenging to apply, because vaccination history may be difficult to ascertain during a disaster, and the risk of tetanus with unspecified trauma might be present. Savioli et al 54 reported that many individuals are not aware of their vaccination history; this is especially the case among the elderly who are reported to be less aware of their vaccination history. Thus, the elderly is a target group for whom TQS could be useful in identifying tetanus morbidity risk according to their study.…”
Section: Disaster Preparedness For Tetanus Treatmentmentioning
confidence: 99%